A STUDENTS’ RELUCTANCE TO SPEAK ENGLISH AT SEVENTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM AT UNIVERSITY OF PASIR PENGARAIAN - Citra Melani; Eripuddin; Pipit Rahayu (JEE (Journal of English Education), 2025)
This research aims to identify the factors contributing to the reluctance of seventh-semester students in the English Study Program at the University of Pasir Pengaraian to speak English. This study employed a descriptive qualitative method. Data were collected through questionnaires and interviews with 16 students who demonstrated a high tendency of reluctance in speaking English. The questionnaire was developed using a Likert scale and covered five main aspects: lack of confidence, shyness, anxiety, lack of motivation, and fear of making mistakes. Interviews were conducted to support and clarify the quantitative findings. The results revealed that most students experience psychological and linguistic barriers that affect their confidence in speaking. The most dominant factors include fear of making mistakes, concern over negative judgment from classmates, and limited vocabulary and pronunciation skills. These findings indicate the necessity for more supportive and interactive teaching approaches that foster speaking confidence. This research is expected to contribute to the development of more effective English language teaching strategies and serve as a reference for future researchers in examining speaking reluctance in the context of higher education